Forms of n‐3 (ALA, C18:3n‐3 or DHA, C22:6n‐3) Fatty Acids Affect Carcass Yield, Blood Lipids, Muscle n‐3 Fatty Acids and Liver Gene Expression in Lambs. Issue 11 (22nd September 2015) - Ponnampalam, Eric N.; Lewandowski, Paul A.; Fahri, Fahri T.; Burnett, Viv F.; Dunshea, Frank R.; Plozza, Tim; Jacobs, Joe L.
Abstract: The effects of supplementing diets with n‐3 alpha‐linolenic acid (ALA) and docosahexaenoic acid (DHA) on plasma metabolites, carcass yield, muscle n‐3 fatty acids and liver messenger RNA (mRNA) in lambs were investigated. Lambs ( n = 120) were stratified to 12 groups based on body weight (35 ± 3.1 kg), and within groups randomly allocated to four dietary treatments: basal diet (BAS), BAS with 10.7 % flaxseed supplement (Flax), BAS with 1.8 % algae supplement (DHA), BAS with Flax and DHA (FlaxDHA). Lambs were fed for 56 days. Blood samples were collected on day 0 and day 56, and plasma analysed for insulin and lipids. Lambs were slaughtered, and carcass traits measured. At 30 min and 24 h, liver and muscle samples, respectively, were collected for determination of mRNA (FADS1, FADS2, CPT1A, ACOX1) and fatty acid composition. Lambs fed Flax had higher plasma triacylglycerol, body weight, body fat and carcass yield compared with the BAS group ( P < 0.001). DHA supplementation increased carcass yield and muscle DHA while lowering plasma insulin compared with the BAS diet ( P < 0.01). Flax treatment increased ( P < 0.001) muscle ALA concentration, while DHA treatment increased ( P < 0.001) muscle DHA concentration. Liver mRNA FADS2 was higher and CPT1A lower in the DHA group ( P < 0.05). The FlaxDHA diet had additive effects, including higher FADS1 and ACOX1 mRNA than for the Flax or DHA diet. In summary, supplementation with ALA or DHA modulated plasma metabolites, muscle DHA, body fat and liver gene expression differently.